Fishery aspect of horseshoe Crab [Tachypleus gigas (Müller, 1785)] in the Peninsular Malaysia: exploitation status - Mohd Razak, Mohd Razali; Kassim, Zaleha (Horizon Research Publishing Cooperation, 2017)
Horseshoe crab is a unique Arthropoda which is also known as a living fossil because of its ancient morphological appearance. The animal established its existence since 300 million years ago and maintained its morphology to present day. The greatest proportion of adult horseshoe crab mortality is probably due to human activity. Horseshoe crabs in Malaysia are harvested for local consumption or marketed to the neighbor country. Series of survey were carried out to understand the exploitation status and collection technique of horseshoe crab in selected coast, Pahang and Malacca coastal area. Interviews were carried out with fisherman that involved in horseshoe crab exploitation activities. Data collected from 100 respondents were analyzed to compare the exploitation activity in both coastal areas. Respondents were mostly fisherman which used both techniques; collecting on shoreline and net fishing to catch horseshoe crab. More people significantly (p<0.05) used traditional collection method (hand harvest at shoreline) in Pahang (56.1%) compared to those in Malacca (34.15%). 65.85% collectors in Malacca adopted the netting method while, only 43.9% collectors in Pahang preferred the same method to collect adult horseshoe crabs coming to the shore during spawning season. The frequency of netting method monthly was significantly higher (p<0.05) in Malacca than Pahang. This resulted to the higher horseshoe crab quantities caught by 50 respondents in Malacca (16860 per month) than Pahang (4180 per month). The initial results from this survey indicate an alarming condition faced by the horseshoe crab coming to the beach for nesting. Monitoring program should be planned to sustain the fishery activity on horseshoe crab in Malaysia.